Effortless : make it easier to do what matters most - Mckeown, Greg (New York : Currency, 2021)
Presents a guide to making the most essential tasks in life the easiest to accomplish by focusing on effortless action, simplifying decision-making, and achieving results without burnout.
Companion to the author$1 (Bs previous book, Essentialism.s
Includes bibliographical references.
Keywords: Success -- Psychological aspects; Self-management (Psychology).; Work-life balance; Time management